Re-interpreting Deuteronomy to Empower Women (of South Africa) - Pietersen, Christo (Old Testament Essays, 2022)
The patriarchal discourse in the Deuteronomic Code creates the need for its re-interpretation from a feminist perspective. This is in aid of understanding the subordination of women viewed from the following perspectives: their roles, images and the limited contributions of women in the ancient world. The reading also includes some remarks on the patrilineal and patriarchal organisation of the Israelite society and its family-centred economy – with special reference to the Covenant Code because of its similarity to Deuteronomy. This article describes how reformers of the Code formed a social structure which they made effective by linking disempowerment of women with other poverty alleviation laws. https://doi.org/10.17159/2312-3621/2021/v34n3a7